2020
DOI: 10.1126/sciadv.abb2057
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of San Andreas tremors by thermal instabilities below the seismogenic zone

Abstract: The relative motion of tectonic plates is accommodated at boundary faults through slow and fast ruptures that encompass a wide range of source properties. Near the Parkfield segment of the San Andreas fault, low-frequency earthquakes and slow-slip events take place deeper than most seismicity, at temperature conditions typically associated with stable sliding. However, laboratory experiments indicate that the strength of granitic gouge decreases with increasing temperature above 350°C, providing a possible mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…However, more imminent seismic hazard in Kathmandu may originate from seismic ruptures that break different sections of the Himalayan megathrust, initiating outside the Kathmandu Klippe 7 . Different scenarios of future seismicity are also possible due to the many remaining unknown mechanical properties of the plate boundary, including deformation of the upper plate by faulting and folding 8,48 , more complex frictional behaviour of the megathrust 49 , and interactions with other segments of the Himalayan megathrust 50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, more imminent seismic hazard in Kathmandu may originate from seismic ruptures that break different sections of the Himalayan megathrust, initiating outside the Kathmandu Klippe 7 . Different scenarios of future seismicity are also possible due to the many remaining unknown mechanical properties of the plate boundary, including deformation of the upper plate by faulting and folding 8,48 , more complex frictional behaviour of the megathrust 49 , and interactions with other segments of the Himalayan megathrust 50 .…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that variations in potency density among slow‐slip events preclude a simple characterization in terms of a linear or cubic root scaling between moment and duration. Several micro‐physical mechanisms of deformation may be responsible for the slow‐slip phenomenon, including stable weakening (Liu & Rice, 2005, 2007; Veedu & Barbot, 2016), dilatant hardening (Segall et al, 2010), semi‐brittle deformation (Goswami & Barbot, 2018), fluid pulses (Cruz‐Atienza et al, 2018), and thermal instabilities (Wang & Barbot, 2020). In addition, some slow‐slip events do not occur spontaneously but are triggered by distant seismic events (Zigone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…
Slow earthquakes are mainly observed in regions surrounding seismogenic zones, which are the areas that rupture in large regular earthquakes, along the plate boundaries of subduction zones (e.g., Obara & Kato, 2016) or strike-slip faults (e.g., Nadeau & Dolenc, 2005;Wang & Barbot, 2020). Various types of slow earthquakes, such as low frequency tremors (tectonic tremors; e.g., Obara, 2002), low frequency earthquakes (LFEs; e.g., Shelly et al, 2006), very low frequency earthquakes (VLFEs; e.g., Obara & Ito, 2005), and slow slip events (SSEs; e.g., Dragert et al, 2001) have been observed in many subduction zones.
…”
mentioning
confidence: 99%